(untitled) (Research, Society and Development, 2022)
The general objective of the study was to verify the epidemiological profile of users of a public emergency room classified as non-urgent, before and after the Covid-19 pandemic and the specific objective was to analyze the situation considering the academic and professional interest in the subject, aiming to contribute to the quality of care provided in the Brazilian Unified Health System. The methodology included integrative review, approval in ethics committee and data sheet (gender, age, day, time, municipality, neighborhood and complaint) of the hospital archive, including all participants with full entry bulletin, ending with statistical analysis and report. The study showed that, in 2019, the Service assisted both men and women, being children and adults, on a working day, morning and afternoon, residents in the capital, coming from nearby neighborhoods and the most populous neighborhoods and complaining of traumatology, medical clinic and specialized care. In 2020/2021, the attendance was of men and women, being adults, on a working day, morning and afternoon hours, residents in the capital, nearby neighborhoods and with complaints of physical trauma and chest pain. With the Covid-19 pandemic, although the number of users classified as non-urgent was three times lower than in 2019, they resorted to the emergency room, appearing men and women, adults, during morning and afternoon, on a working day, living in the capital, in nearby neighborhoods and with complaints of physical trauma and chest pain.